FRI0110 Epcs is A Determinant of Vascular Function and Atherosclerosis in As. (10th June 2014) - Syngle, A.; Garg, N.; Verma, I.; Krishan, P.
Abstract : Background: Ankylosing Spondylitis (AS) is an inflammatory disease associated with premature atherosclerosis. 1 We hypothesized that depleted endothelial progenitor cells (EPCs), mediators of inflammation and Carotid intima media thickness (cIMT) are associated with atherosclerosis in other populations 2 and would be increased and associated with the severity of atherosclerosis in patients with AS. Objectives: The aim of this study was to assess EPC population, and its potential relationships with inflammatory cytokines, vascular function and marker of atherosclerosis in AS. Methods: We compared 30 patients of AS with 22 healthy controls. CD34 +, CD133+, were used to quantify EPCs using flow-cytometry. Flow-mediated dilatation (FMD) was assessed by using Angiodefender™ (Everest Genomic Ann Arbor, MI, United States). Carotid intima media thickness (cIMT) was measured using ultrasonography. Pro-inflammatory cytokines, TNFalpha, IL-1, IL-6, and inflammatory disease activity measures Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and Functional ability was monitored by using Bath Ankylosing Spondylitis Functional Index (BASFI) were also assessed. Results: EPCs were significantly decreased in AS patients as compared to healthy controls (p=0.01). We also found significantly increased CIMT in AS group compared with controls (p=0.01). FMD was significantly impaired and inflammatory disease activity measures i.e. BASDAI, BASFI and serum concentrations of IL-6, TNF-α and IL-6 were higher in AS patients than controls (all P<0.05). Total cholesterol and high density lipoprotein cholesterol levels are significantly impaired in AS patients than controls (P<0.05). Significant positive correlation was observed between the percentage of EPCs, FMD and HDL cholesterol (P<0.05) and negative correlation was found between EPC and CIMT, IL-6, and BASDAI. Conclusions: EPCs are significantly associated endothelial dysfunction and subclinical atherosclerosis in AS. EPC depletion in AS possibly results from severe disease and elevated IL-6. Higher CV risk in AS is possibly also contributed by reduced EPCs, altered lipid profile and higher level of pro-inflammatory cytokines. Impaired EPC may lead to accelerated vascular remodelling due to chronic impairment of endothelial function. References: Ross R. N Engl J Med. 1999;340:115–126. Tanasescu C et al. Rom J Intern Med. 2009;47:103-108. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5228